Umberto Nobile between two totalitarianisms - Zani Luciano (Routledge, 2023)
Umberto Nobile was a well-known airship designer and pilot who was the key protagonist in Italy’s mission during the 1920s to establish itself as a dominant player in the airship industry. He became a popular hero of Italian Fascism after his spectacular flight over the North Pole in the airship Norge in 1926. Two years later, in 1928, his reputation was destroyed by the tragedy of the airship Italia, which crashed on the ice pack in an attempt to replicate the Norge’s successful flight. Having been denigrated, humiliated and rejected by the regime that had exalted him, Nobile resigned from the Air Force and accepted the invitation of Soviet authorities to build the Soviet airship industry from the ground up, but his experience in the Soviet Union ended up following the same parabola from exaltation to failure as his experience in Italy. 1 I want to put Nobile’s personal vicissitudes against the backdrop of the epic battle for the domination of the sky between the airplane and the airship, as well as within the context of the competition/confrontation between two totalitarian regimes which frequently displayed contradictory characteristics of collaboration and rivalry, affinity and animosity.